2023
DOI: 10.1111/eci.14046
|View full text |Cite
|
Sign up to set email alerts
|

External stenting for saphenous vein grafts in coronary artery bypass grafting: A meta‐analysis

Abstract: ObjectivesAutologous saphenous vein grafts (SVGs) are the most commonly used bypass conduits in coronary artery bypass grafting (CABG) with multivessel coronary artery disease. Although external support devices for SVGs have shown promising outcomes, the overall efficacy and safety remains controversial. We aimed to evaluate external stenting for SVGs in CABG versus non‐stented SVGs.MethodsMEDLINE, EMBASE, Cochrane Library and clinicaltrails.gov were searched for randomized controlled trials (RCTs) to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…A follow-up of 4.5 years ("the VEST IV trial") has been reported in 21 patients from the VEST I trial; external stenting significantly reduced diffuse intimal hyperplasia and the development of lumen irregularities; however, graft failure rates were still comparable between stented and non-stented groups [63]. Other meta-analyses [64,65] and a review [13] have reported similar conclusions. Larger trials with longer follow-ups are warranted to determine whether the positive remodeling effects might translate into clinical benefits [6,9].…”
Section: Coronary Artery Bypass Graftingmentioning
confidence: 84%
“…A follow-up of 4.5 years ("the VEST IV trial") has been reported in 21 patients from the VEST I trial; external stenting significantly reduced diffuse intimal hyperplasia and the development of lumen irregularities; however, graft failure rates were still comparable between stented and non-stented groups [63]. Other meta-analyses [64,65] and a review [13] have reported similar conclusions. Larger trials with longer follow-ups are warranted to determine whether the positive remodeling effects might translate into clinical benefits [6,9].…”
Section: Coronary Artery Bypass Graftingmentioning
confidence: 84%
“…Next, overdistending the vein conduits with supra-physiological pressures to check for leaks or to increase the lumen of the veins should be abandoned from clinical practice. However, it has to be acknowledged that currently, the utilization of, yet cost-intensive, pressure-controlled syringes in large parts of the world pose an important economical burden ( 129 ).…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, where the trajectory suggests potential vein graft stenosis or failure, an additional graft stenting procedure becomes a necessity. This intervention aims to mitigate the intimal hyperplasia area and thickness, enhancing lumen uniformity—an aspect assessed with the Fitzgibbon I classification [ 26 ]. The meticulous consideration of these factors, grounded in the insights from our morphological analysis, emphasizes the intricate balance between the structural attributes of veins and their long-term functionality as conduits in CABG.…”
Section: Discussionmentioning
confidence: 99%